Editorial. Public Transformations: Infrastructure, Ecology, Law, and Management in Modern Society - Nesterak, Janusz; Ziębicki, Bernard (Journal of Public Governance, 2023)
In this issue of our journal, we present five exceptional analyses that explore various dimensions related to infrastructure, ecology, governance, and legal regulations within the public sphere. These articles address issues such as transport exclusion, the role of telemedicine in environmental protection, integrated safety management of large-scale cultural events, the interpretation of legal norms for municipal companies, and the impact of urban transport infrastructure on the users’ sense of safety. Each of these topics contributes important insights and recommendations, which, while varied in focus, collectively create a cohesive picture of contemporary challenges and directions for development in public governance.